In-situ tuning of catalytic activity by thermoelectric effect - Achour, Abdenour (Cranfield University, 2017)
For the first time, a new type of reactor which can combine thermoelectric energy harvesting and electrochemical promotion of catalysis was developed. A novel use of thermoelectric material as a catalyst support and promoter was investigated. A facile, cost-effective and scalable synthesis of thermoelectric material BiCuSeO has been developed. It was discovered that the catalytic activity of Pt supported on the thermoelectric material BiCuSeO, through the ethylene oxidation, can be increased by several tens to several hundreds of times by a thermoelectric voltage. We call this Thermoelectric Promotion of Catalysis (TEPOC). The catalytic activity under fuel-lean and fuel-rich conditions was also investigated for ethylene oxidation. It is believed that oxygen was more strongly and C₂H₄ was weakly adsorbed on the catalyst Pt surface under lean-fuel conditions (O₂/C₂H₄ > 1). However, under rich-fuel conditions (C₂H₄/O₂> 1.4), C₂H₄ became strongly adsorbed (probably chemisorbed) to the surface especially at a high Seebeck voltage, this blocked the catalyst surface, reduced the catalytic active site, hence the rate became smaller. To further investigate the TEPOC effect, the CO₂ hydrogenation over the same catalysts supported on the thermoelectric BiCuSeO was also studied and the results confirmed similar significant promotional effect. It also was found that a negative thermoelectric voltage shifted chemical equilibrium towards the reverse water gas shift (RWGS) reaction and CO selectivity. As a results, the CO₂ hydrogenation conversion reached 48.4% (CO₂:H₂ = 1:4) with 100% CO selectivity for Pt(80)/BCSO at 656 K, which was above the thermodynamic equilibrium conversion (TEC) under no Seebeck voltage without methanation. It was established a linear relationship between Ln(r) and –eV/kьT, where –eV/kьT is the ratio between the extra electrochemical energy induced by thermoelectric effect and the thermal energy of an electron. From this it was derived that the promotional effect was attributed to the change of work function of the catalyst surface, accompanied by charge transfer from the bulk to the surface due to the thermoelectric effect. ii The discovery of TEPOC prompts that many catalytic chemical reactions can be tuned in-situ and independently from the change of conditions within the reaction chamber, to achieve much higher reaction rate, or at lower temperature, or have better desired selectivity through changing the backside temperature of the thermoelectric catalyst support.
Keywords: Heterogeneous catalysis; catalyst promoters; BiCuSeO; thermoelectric effect; thermoelectric promotion of catalysis